The Hellenistic court : monarchic power and elite society from Alexander to Cleopatra - Erskine, Andrew; Llewellyn-Jones, Lloyd; Wallace, Shane, 1982- (Classical Press of Wales, The, 2017)
Hellenistic courts were centres of monarchic power, social prestige and high culture in the kingdoms that emerged after the death of Alexander. They were places of refinement, learning and luxury, and also of corruption, rivalry and murder. Surrounded by courtiers of varying loyalty, Hellenistic royal families played roles in a theatre of spectacle and ceremony. Architecture, art, ritual and scholarship were deployed to defend the existence of their dynasties. The present volume, from a team of international experts, examines royal methods and ideologies. It treats the courts of the Ptolemies, Seleucids, Attalids, Antigonids and of lesser dynasties. It also explores the influence, on Greek-speaking courts, of non- Greek culture, of Achaemenid and other Near Eastern royal institutions. It studies the careers of courtesans, concubines and 'friends' of royalty, and the intellectual, ceremonial, and artistic world of the Greek monarchies. The work demonstrates the complexity and motivations of Hellenistic royal civilisation, of courts which governed the transmission of Greek culture to the wider Mediterranean world - and to later ages.